2016
DOI: 10.1186/s12889-016-2739-0
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial changes in food consumption and nutrient intake after 10 years of follow-up in a Mediterranean cohort: the SUN project

Abstract: BackgroundThe assessment of changes in dietary habits provides interesting information on whether or not the observed trends are in line with accepted nutritional guidelines. The objective was to evaluate within-subject longitudinal changes in food consumption and nutrient intake and in a 10-year follow-up study.MethodsThe SUN (Seguimiento Universidad de Navarra) project is a prospective Spanish cohort study. Diet was assessed using a 136-item food-frequency questionnaire (FFQ), previously validated in Spain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 52 publications
3
11
0
1
Order By: Relevance
“…A similar study whose results can be compared to ours has been reported by the Danish MONICA project, even though the follow-up period did not cover the same calendar period as our study [ 11 , 12 , 13 ]. The cohort population of this study was drawn from random, age-stratified samples of 30, 40, 50 and 60 years of age at recruitment and had a 10 year follow-up period (1982–1992).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…A similar study whose results can be compared to ours has been reported by the Danish MONICA project, even though the follow-up period did not cover the same calendar period as our study [ 11 , 12 , 13 ]. The cohort population of this study was drawn from random, age-stratified samples of 30, 40, 50 and 60 years of age at recruitment and had a 10 year follow-up period (1982–1992).…”
Section: Discussionsupporting
confidence: 73%
“…Although the above studies are not identical as far as mean age at baseline or their calendar period, it is important to note the fact that in all studies, the participants report an overall tendency of healthier nutritional habits with the passage of time [ 11 , 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…(Reynolds, Cousins, Newell, & Imrie, 2013 ) in work exploring the impact on social relations of the proximity of trial staff to community members affecting HIV surveillance in South Africa, we emphasize that it is imperative to understand these potential implications when designing interventions that rely on and in turn, influence for the future, social relations between communities participating in the research and those charged with delivering it. Communities need to be understood not as homogenous and harmonious, but as diverse groupings with ongoing inequalities and power relationships (Enria et al., 2016 ) and community-based research should understand these underlying inequalities and power differentials and their potential impact on them.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to score lipid intake, the monounsaturated to saturated fatty acids ratio is calculated. Since its creation, the MDScale has been used in hundreds of studies in Mediterranean and non-Mediterranean countries, including studies involving the Spanish cohort and the SUN project in which the MDScale was used to assess changes in dietary habits after a follow-up period of 10 years [22]. In a study conducted in 2015 in the United States, a high adherence to the MD, as assessed by using the MDScale, was associated with a low risk of cardiovascular disease [23].…”
Section: Methodsmentioning
confidence: 99%